Secret Seven - Blyton, Enid (London: Hodder Children's Books, 2015)
It's their very first adventure and the secret seven super-sleuths are already on the trail of a mystery! the gang are dressed in disguise, following a lead to a spooky old house in the snow.
Keywords: Children's stories